Enteroparasitosis in patients attended by the health public service: epidemiology and spatial distribution - Ibiapina, Andressa Barros; Leal, Janaína Soares; Santana, Pedro Ricardo Alves de; Mesquita, Marcelo Ribeiro; Lopes, Tito Lívio da Cunha; Braz, Débora Cavalcante (Scientia Medica, 2020)
Aims: This research aims to determine the epidemiology and the spatial distribution of intestinal parasitosis in the city of Teresina, Brazil. Methods: A cross-sectional study was carried out based on the data of parasitological fecal exams performed in the Laboratory Raul Bacelar between January, 2014 and July, 2017. In addition to the prevalence of intestinal parasitosis and polyparasitism, we verified the association of these diseases with gender, zone and period of the year by means of the chi-squared test, whereas the relation with age was analyzed by the Mann-Kendall tests and multiple comparisons of age classes. The spatial distribution was performed using the QGIS georeferencing software. Results: The prevalence of enteroparasitosis in Teresina was 17.8% with Ascaris lumbricoides being the most common species. The prevalence of individuals with polyparasitism was 3.1%, in which an association between the species Entamoeba coli and Entamoeba histolytica/dispar was found. There was no relation between intestinal parasitosis with gender, but we verified that individuals in rural areas were more susceptible to these diseases. The species Ascaris lumbricoides and Entamoeba histolytica/dispar occured more frequently in the first and second semester, respectively. We observed that there was an apparent tendency to increase cases of Entamoeba histolytica/dispar and reduction of cases of Giardia sp. according to aging. Mapping intestinal parasitosis showed us that there was a prevalence between 1 and 20% in most of Teresina’s neighborhoods, and Ascariasis embodies at least 40% of cases of enteroparasitosis in these neighborhoods. Conclusions: Investments in basic sanitation and new epidemiological investigations must be carried out to control intestinal parasitosis in Teresina, emphasizing that children and the elderly should be considered priority groups in these programs. ***Enteroparasitoses em pacientes atendidos pelo serviço público de saúde: epidemiologia e distribuição espacial*** Objetivo: Determinar a epidemiologia e a distribuição espacial das parasitoses intestinais no município de Teresina, Brasil. Métodos: Foi realizado um estudo transversal com base nos resultados dos exames parasitológicos de fezes executados no laboratório Raul Bacelar, entre janeiro de 2014 e julho de 2017. Além da prevalência de parasitoses intestinais e de poliparasitismo, verificou-se a associação destas doenças com sexo, zona e período do ano, por meio do teste do qui-quadrado, enquanto a relação com a idade foi analisada pelos testes de Mann-Kendall e comparações múltiplas de faixas etárias. A distribuição espacial foi realizada utilizando o software de georreferenciamento QGIS. Resultados: A prevalência de enteroparasitoses em Teresina foi de 17,8%, sendo Ascaris lumbricoides a espécie mais comum. A prevalência de indivíduos com poliparasitismo foi de 3,1%, na qual foi encontrada uma associação entre as espécies Entamoeba colie Entamoeba histolytica/dispar. Não houve relação entre parasitoses intestinais e sexo, mas verificou-se que indivíduos na zona rural foram mais suscetíveis a essas doenças. As espécies Ascaris lumbricoides e Entamoeba histolytica/dispar ocorreram com maior frequência, respectivamente, no primeiro e no segundo semestre. Observou-se que houve aparente tendência de aumento de casos de E. histolytica/dispar e de redução de casos de Giardia sp. de acordo com o envelhecimento. O mapeamento das parasitoses intestinais demostrou que houve uma prevalência entre 1 e 20% na maioria dos bairros de Teresina, e a ascaridíase representou pelo menos 40% dos casos de enteroparasitose nesses bairros. Conclusões: Investimentos em saneamento básico e novas investigações epidemiológicas devem ser realizados para o controle das parasitoses intestinais em Teresina, enfatizando que crianças e idosos devem ser considerados grupos prioritários nessas ações. Palavras-chave: Epidemiologia; mapeamento geográfico; helmintíase; doenças negligenciadas; doenças parasitárias; infecções por protozoários; saneamento.